2019
DOI: 10.7150/ntno.39514
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble enhanced ultrasound for the antivascular treatment and monitoring of hepatocellular carcinoma

Abstract: Background and Objective: Hepatocellular carcinoma (HCC) is the most common primary liver malignancy, and its current management relies heavily on locoregional therapy for curative therapy, bridge to transplant, and palliative therapy. Locoregional therapies include ablation and hepatic artery therapies such as embolization and radioembolization. In this study we evaluate the feasibility of using novel antivascular ultrasound (AVUS) as a noninvasive locoregional therapy to reduce perfusion in HCC lesions in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…In addition to using a diagnostic ultrasound device for treatment, we also chose to use a mouse model that could appropriately mimic human liver cancer. Despite previous reports showing efficacy in ultrasound-mediated vascular disruption with or without drug delivery (Wood et al, 2005;Goertz et al, 2012;Liu et al, 2012;D'Souza et al, 2019), there have been no studies using a physiologically relevant preclinical liver cancer model. However, one drawback to using this model is the substantial time to tumorigenesis (40 weeks in addition to breeding time).…”
Section: Pten-null Mice Are An Appropriate Model For Studying Image-gmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to using a diagnostic ultrasound device for treatment, we also chose to use a mouse model that could appropriately mimic human liver cancer. Despite previous reports showing efficacy in ultrasound-mediated vascular disruption with or without drug delivery (Wood et al, 2005;Goertz et al, 2012;Liu et al, 2012;D'Souza et al, 2019), there have been no studies using a physiologically relevant preclinical liver cancer model. However, one drawback to using this model is the substantial time to tumorigenesis (40 weeks in addition to breeding time).…”
Section: Pten-null Mice Are An Appropriate Model For Studying Image-gmentioning
confidence: 99%
“…Previous studies that have examined ultrasound-mediated vascular disruption with or without drug delivery in vivo have generally used simplistic single element transducers for the ultrasound treatment which limits clinical translation (Goertz et al, 2012;Ho et al, 2018;D'Souza et al, 2019). Single element focused transducer systems provide a great deal of flexibility for parameter optimization, but they are cumbersome to use due to requiring auxiliary components (function generators, amplifiers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…On the topic of oxygen delivery for radiotherapy, Fix et al has previously shown that a 30% increase in tumoral hemoglobin saturation is sufficient to achieve a ~30% reduction in tumor growth rate by injection of ~3×10 10 OMBs/kg directly into the tumor [29]. For intravenous, as opposed to intratumoral administration, we see a constraint on OMB concentration (<5×10 8 OMB/mL) due to handling considerations related to excessive viscosity at high OMB concentrations.…”
Section: Discussionmentioning
confidence: 86%
“…1A). The dual nature of microbubbles for imaging and therapy provides a vehicle for ultrasound-mediated nanotheranostics [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, shear forces can damage surrounding vascular endothelial cells, leading to sphingomyelinase-related, ceramide-induced apoptosis. 12,13 Preclinical studies have demonstrated antitumor effects both with USMBs alone 14 and combining USMBs with external beam radiotherapy (XRT) to achieve synergistic effects. 11 Studies have demonstrated that USMBs are effective radioenhancement agents for a variety of cell types in vivo, such as breast, prostate, leukemia, and sarcoma tumors, 15 with additive-to-synergistic effects seen for combinations of USMBs and XRT.…”
mentioning
confidence: 99%